Analysis of Students’ Difficulties in Reading English Text for EFL Learners in Junior High School - Widy Silva Julianti; Masrupi Masrupi; Yusti Fargianti (Jambura Journal of Community Empowerment, 2026)
This study aims to analyze the reading difficulties faced by EFL students at the junior high school level. Using a qualitative descriptive method with content analysis, data were gathered through interviews and classroom observations involving 20 eighth-grade students and one English teacher at SMPN 3 Bantarujeg. The findings show that students experience difficulties in vocabulary mastery, sentence structure comprehension, identifying main ideas, making inferences, and applying reading strategies. In addition, teacher-centered approaches and lack of support from the learning environment contribute to these issues. The study recommends the implementation of strategy-based instruction and supportive classroom practices to improve students’ reading comprehension.